Prevalence of SARS‐CoV‐2 antibodies among nurses: A systematic review and meta‐analysis. Issue 11 (27th September 2021) - He, Steven; Hecimovic, Anthony; Matijasevic, Vesna; Mai, Ha Thi; Heslop, Linda; Foster, Jann; Alexander, Kate E.; Pal, Naru; Alexandrou, Evan; Davidson, Patricia M.; Frost, Steven A.
Abstract: Aims and Objectives: This systematic review and meta‐analysis reports the seroprevalence of SARS‐CoV‐2 antibodies among nurses. Background: With a growing body of literature reporting the positive serology for SARS‐CoV‐2 antibodies among healthcare workers, it remains unclear whether staff at the point of direct patient care are more prone to developing and transmitting the virus. Given nurses make up the majority of the global health workforce, outbreaks among these workers could severely undermine a health system's capability to manage the pandemic. We aimed to summarise and report the seroprevalence of SARS‐CoV‐2 antibodies among nurses globally. Design: Systematic review and meta‐analyses. Methods: This systematic review was developed, undertaken and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guideline. We searched the electronic medical literature databases: MEDLINE; CINAHL; and EMBASE for studies reporting the seroprevalence of SARS‐CoV‐2 antibodies among nursing staff. Studies that reported nursing specific data were included in this review. Study quality was evaluated using the Joanna Briggs Institute checklist for studies reporting prevalence data. Studies were stratified according to the World Health Organisation region classifications, and results were presented using forest plots and summary prevalence and variance was estimated using a random effects model. Results: Our electronic search identified 1687 potential studies, of which 1148 were screened for eligibility after duplicates were removed, and 51 of the studies were included in our meta‐analysis. The overall seroprevalence of SARS‐CoV‐2 antibodies among nurses was estimated to be 8.1% (95% CI 6.9%–9.4%) among the 60, 571 participants included in the studies. Seropositivity was highest in the African region (48.2%, 95% CI 39.2%–57.3%), followed by the European region (10.3%, 95% CI 8.0%–12.5%), the Region of the Americas (8.4%, 95% CI 6.0%–10.7%), the South‐East Asia region (3.0%, 95% CI 0.00%–6.5%) and the Western Pacific region (0.5%, 95% CI 0.0%–1.0%). Pooled estimates were unable to be calculated in the Eastern Mediterranean region due to insufficient studies. Conclusion: The seroprevalence of SARS‐CoV‐2 antibodies among nurses is comparable to other healthcare workers, and possibly similar to the general population. Early adoption and adherence to personal protective equipment and social distancing measures could explain these similarities, meaning the majority of staff contracted the virus through community transmission and not in a healthcare setting. Relevance to clinical practice: Fear and uncertainty have been features of this pandemic, including among nurses. This meta‐analysis should provide some comfort to nurses that risks are similar to community exposure when adequate PPE is available and there is an adherence to infection control measures.